2016
DOI: 10.1038/jhg.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in glaucoma and neurodegenerative diseases

Abstract: MicroRNAs (miRNAs) constitute a class of short, non-coding RNAs, which have important role in post-transcriptional regulation of genes expression by base-pairing with their target messenger RNA (mRNA). In recent years, miRNAs biogenesis, gene silencing mechanism and implication in various diseases have been thoroughly investigated. Many scientific findings indicate the altered expression of specific miRNA in the brains of patients affected by neurodegenerative diseases (NDs) such as Alzheimer's disease, Parkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 97 publications
0
45
0
1
Order By: Relevance
“…Several studies 8,9,15 have shown previously the contribution of miRNAs to the pathophysiology of POAG. However, these studies are mainly focused on differentially expressed miRNAs indentified by miRNA profiling in a small number of samples, which makes it difficult to interpret their results to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies 8,9,15 have shown previously the contribution of miRNAs to the pathophysiology of POAG. However, these studies are mainly focused on differentially expressed miRNAs indentified by miRNA profiling in a small number of samples, which makes it difficult to interpret their results to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…7 There are strong indications that miRNAs play important roles in the pathogenesis of POAG. 811 For example, miR-29b and miR-24 are involved in gene regulation in trabecular meshwork cells. 12 Moreover, the miRNA expression levels have been linked to maintaining the balance of the aqueous humor, the change in the trabecular meshwork, and the apoptosis of the retinal ganglion cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many scientific findings indicate that dysregulation of some specific miRNAs may be associated with pathogenesis of neurodegenerative diseases including PD [28]. miR-22 overexpression exhibited neuroprotective and reversal effects on a 6-hydroxydopamine- (6-OHDA-) induced cell model of PD by targeting transient receptor potential melastatin 7 (TRPM7) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one miR can regulate up to 30 mRNAs and one mRNA can be regulated by several miRs; then, an alteration of miR expression can regulate several processes. A deregulation of miR expression has been found in several pathologies, including glaucoma, neurodegenerative diseases [94], cardiovascular pathologies [95], metabolic diseases [96] and cancer [97], among others. Since deregulation in miR expression is crucial for cancer development [98,99], the roles of miR in this pathology are divided into two groups: oncomiRs and tumor suppressor miRs [100].…”
Section: Micrornas and Cancermentioning
confidence: 99%